2011
DOI: 10.1007/978-3-642-21257-4_28
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection in Regression Tasks Using Conditional Mutual Information

Abstract: Abstract. This paper presents a supervised feature selection method applied to regression problems. The selection method uses a Dissimilarity matrix originally developed for classification problems, whose applicability is extended here to regression and built using the conditional mutual information between features with respect to a continuous relevant variable that represents the regression function. Applying an agglomerative hierarchical clustering technique, the algorithm selects a subset of the original s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The contributions of this paper are two-fold: (a) to establish a methodology to properly solve the estimation of this distance for regression problems where the relevant variable is continuous, through the assessment of the conditional mutual information between input and output variables; and (b) to show the extension of this methodology to multi-output regression datasets. Some preliminary results were presented in [12], where the method was applied only to single-output regression datasets. In addition, the work presented here introduces an information theoretic framework for the distance used in the clustering-based feature selection process in regression tasks, when using continuous variables.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of this paper are two-fold: (a) to establish a methodology to properly solve the estimation of this distance for regression problems where the relevant variable is continuous, through the assessment of the conditional mutual information between input and output variables; and (b) to show the extension of this methodology to multi-output regression datasets. Some preliminary results were presented in [12], where the method was applied only to single-output regression datasets. In addition, the work presented here introduces an information theoretic framework for the distance used in the clustering-based feature selection process in regression tasks, when using continuous variables.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, it was shown that the mutual information criterion fails to select optimal features in some situations. Feature clustering-based methods aiming to find a subset of the features that minimizes the regression error using conditional MI has been proposed ( [45], [46], [47]) as an approach for the application of MI in regression problems. These studies show the efficacy of MI to perform in regression task with suitable stopping criteria.…”
Section: Reviewsmentioning
confidence: 99%